STUDY OF MANGROVE VEGETATION COMMUNITY AT BUNAKEN NATIONAL PARK AREA, TELING VILLAGE - Febiola Gabriela Tular; Helen J Lawalata; Marthy L. S. Taulu (Indonesian Biodiversity Journal, 2022)
Mangrove vegetation generally grows to form a zoning starting from a beach to a view of meters inland. Mangrove zoning consists of Avicennia plant species that face directly toward the sea and behind or on the edge of the Avicennia plant. There is the Riophora plant. Towards the mainland, there are Bruguiera plants and, finally, the Ceriops plant which grows and interacts with small bushes. Each type of Mangrove plant has a level; the first is the seedling level, the second is the sapling level, the third is the pole level, and the fourth is the tree level. This study aims to analyze the Mangrove Vegetation Community in Bunaken Nation Park, Teling Village, using a descriptive survey method and constructing three transects, which are transected measuring 10×10 m2, 5×5 m2, and 2×2 m2. The result on each transect shows that in Bunaken National Park, Teling Village, there were types of Mangrove Vegetation Communities, namely Avicennia plant species with a total of 129, Rhizophora plant species with a capacity of 122 and Bruguiera plant species with a total of 91, where each plant type it has levels with different numbers.